Towards the Continuous Manufacturing of Liquisolid Tablets Containing Simethicone and Loperamide Hydrochloride with the Use of a Twin-Screw Granulator - Daniel Zakowiecki; Margarethe Richter; Ceren Yuece; Annika Voelp; Maximilian Ries; Markos Papaioannou; Peter Edinger; Tobias Hess; Krystyna Mojsiewicz-Pieńkowska; Krzysztof Cal (MDPI AG, 2023)
Continuous manufacturing is becoming the new technological standard in the pharmaceutical industry. In this work, a twin-screw processor was employed for the continuous production of liquisolid tablets containing either simethicone or a combination of simethicone with loperamide hydrochloride. Both active ingredients present major technological challenges, as simethicone is a liquid, oily substance, and loperamide hydrochloride was used in a very small amount (0.27% w/w). Despite these difficulties, the use of porous tribasic calcium phosphate as a carrier and the adjustment of the settings of the twin-screw processor enabled the optimization of the characteristics of the liquid-loaded powders and made it possible to efficiently produce liquisolid tablets with advantages in physical and functional properties. The application of chemical imaging by means of Raman spectroscopy allowed for the visualization of differences in the distribution of individual components of the formulations. This proved to be a very effective tool for identifying the optimum technology to produce a drug product.